I Should be able to Live My Best Life: On Making Meaning of Academic Survival - Casado Perez, Javier F.; Aksoy, Ravza Nur (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
For minoritized faculty, the academic profession can be no less characterized by encounters with oppression than their private lives. We deployed critical phenomenology to understand what participants' (N = 8) meaning making of institutional oppression reveals about their movement from professional disillusionment to reengagement. Our critical hermeneutic analysis of in-depth phenomenological profiles produced three key transformations in participants' pursuit of academic survival: embodied experience, boundary-drawing, and narrative self-definition. We discuss implications for bystander intervention, counterspaces, and life-course mentorship.
Keywords: Institutional life; operative intentionality; institutional oppression; academic survival; FACULTY; COLOR; EXPERIENCES; VOICES; WOMEN; STRATEGIES; RESISTANCE; EDUCATION; IDENTITY; GENDER; Education & Educational Research